2018
DOI: 10.4236/ce.2018.914176
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Strategies Used by Secondary Schools Students in Enhancing Speaking Skills

Abstract: Mastering English as the second language has been a constant challenge for speakers of other languages. Malaysians, especially school students who are from suburban and rural areas are persistently struggling to fulfill the demands of becoming competent English language speakers. Students' low self-confidence and unfamiliarity with language structures hinder their potential to improve their speaking skills. Hence, there is a need to discover the students' most preferred strategies to enhance their speaking ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Abraham & Vann, 1987;Chamot et al, 1996as cited in O'Malley et al, 1985Kiu & Yamat, 2020). In Kiu & Yamat's (2020) study of ESL primary students in Malaysia, it was revealed that the good learners used more strategies for active involvement and more frequently than did their weak learner counterparts, which was similar to Zakaria et al (2018) research findings among secondary school students in Malaysia too. Likewise, many studies showed that successful language learners consistently used a greater variation of language learning strategies (e.g.…”
Section: Successful Language Learnerssupporting
confidence: 63%
See 2 more Smart Citations
“…Abraham & Vann, 1987;Chamot et al, 1996as cited in O'Malley et al, 1985Kiu & Yamat, 2020). In Kiu & Yamat's (2020) study of ESL primary students in Malaysia, it was revealed that the good learners used more strategies for active involvement and more frequently than did their weak learner counterparts, which was similar to Zakaria et al (2018) research findings among secondary school students in Malaysia too. Likewise, many studies showed that successful language learners consistently used a greater variation of language learning strategies (e.g.…”
Section: Successful Language Learnerssupporting
confidence: 63%
“…Some strategies are regarded as effective, yet some others are less effective. Wenden & Rubin (1987) defined learning strategies as "any sets of operations, steps, plans, routines used by the learner to facilitate the obtaining, storage, retrieval and use of information" (p. 19). Oxford (1990) stated that LLS aims to make the language learning process "easier, faster, more enjoyable, more self-directed, more effective and more transferrable to new situations" (p. 8).…”
Section: Literature Review Definition and Classification Of Llsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning speaking skills in the second language has been a daunting task, especially to students who are lacking self-confidence and self-esteem (Zakaria et al, 2018). Therefore, a range of strategies may be used by learners to improve their speaking ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, as opposed to low-performing students, high-performing students used more deliberate and appropriate LLS, (Gani et al, 2015). A research was conducted in a secondary school; where the result showed the most used strategies among the female students had a higher propensity in the use of LLS to improve their speaking skills, (Zakaria et al, 2018).…”
Section: Figure 2 -The Classification Of Language Learning Strategiesmentioning
confidence: 99%